2023
DOI: 10.3390/gels9020117
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Epidermal Growth Factor Loaded Carboxymethylcellulose (EGF-CMC) Hydrogel in Biofilm Formation in Wounds of Diabetic Patients: A Randomized Clinical Trial

Abstract: Diabetic patients frequently develop wounds, which can be colonized by bacteria, mainly Staphylococcus aureus and Pseudomonas aeruginosa, with the ability to form biofilms. This study aimed to evaluate the colonization and biofilm formation of Staphylococcus aureus and Pseudomonas aeruginosa in chronic wounds of diabetic patients treated with a bioactive dressing (EGF-CMC), which consisted of a 2% carboxymethylcellulose (CMC) hydrogel loaded with epidermal growth factor (EGF). This randomized clinical trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In addition, good biocompatibility with L929 fibroblasts was observed, as well as enhanced cell adhesion and proliferation, thus underlining the potential of this hybrid composite scaffold as an attractive wound dressing [ 65 ]. Furthermore, a randomized clinical trial conducted by Pessanha et al demonstrated the effects of a CMC hydrogel loaded with epidermal growth factor (EGF) on biofilm formation in the wounds of patients with DM [ 66 ]. Despite no differences in overall bacterial loads and virulense genes, they revealed that the loaded hydrogels were colonized by bacterial strains that presented lower biofilm formation capacities [ 66 ].…”
Section: Biomaterials As a Promising Therapeutic Platform For Wound D...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, good biocompatibility with L929 fibroblasts was observed, as well as enhanced cell adhesion and proliferation, thus underlining the potential of this hybrid composite scaffold as an attractive wound dressing [ 65 ]. Furthermore, a randomized clinical trial conducted by Pessanha et al demonstrated the effects of a CMC hydrogel loaded with epidermal growth factor (EGF) on biofilm formation in the wounds of patients with DM [ 66 ]. Despite no differences in overall bacterial loads and virulense genes, they revealed that the loaded hydrogels were colonized by bacterial strains that presented lower biofilm formation capacities [ 66 ].…”
Section: Biomaterials As a Promising Therapeutic Platform For Wound D...mentioning
confidence: 99%
“…Furthermore, a randomized clinical trial conducted by Pessanha et al demonstrated the effects of a CMC hydrogel loaded with epidermal growth factor (EGF) on biofilm formation in the wounds of patients with DM [ 66 ]. Despite no differences in overall bacterial loads and virulense genes, they revealed that the loaded hydrogels were colonized by bacterial strains that presented lower biofilm formation capacities [ 66 ].…”
Section: Biomaterials As a Promising Therapeutic Platform For Wound D...mentioning
confidence: 99%
“…Its formation on wound surfaces hampers antibiotic penetration, consequently impeding wound healing. Research indicates that hydrogel can enhance the healing trajectory and management of wounds afflicted by MDR bacteria, particularly those loaded with antibiotics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Covalently cross-linked polymers obtained through the Diels-Alder reaction [14], non-covalently cross-linked non-toxic cryogels of chitosan and polyvinyl alcohol [15], gum arabic cryogels [16], nanofibers based on biodegradable poly-ε-caprolactone, and poly-Llactide obtained via centrifugal spinning or electrospinning [17][18][19][20][21] have been used as gels to prepare wound dressings. Hydrogels based on carboxymethyl cellulose [22] and its combination with carbomer 940 [23], carboxymethyl chitosan [24,25], and chitosan with bacterial cellulose [26] are used to treat chronic wounds and burns.…”
Section: Introductionmentioning
confidence: 99%